Structural basis of positive modulation of type-A GABA receptors - Scott, SJ (2018)
The GABAARs is the main inhibitory neurotransmitter receptor in the brain, and is primarily responsible for maintaining the excitatory-inhibitory balance in neurons on which normal function of the nervous system depends. This receptor is subject to modulation by several endogenous and pharmacological agents, which can have dramatic effects on the brain and behaviour. Common examples of drugs acting GABAARs include anaesthetics, anxiolytics and sedatives. In particular, there has been great interest in developing drugs against the α2- and α3-containing GABAARs because of their roles in pain and anxiety. The aim of the work described in this thesis was to investigate modulation of GABAARs by positive modulators. In particular, because nanobodies raised against GABAARs have previously been shown to positively modulate the α1β3γ2L receptor, new nanobodies were raised against the α2β3 and α3β3 GABAARs, in the hope of obtaining specific modulators. These were characterised for affinity and modulatory activity at their respective GABAARs, and several high-affinity nanobodies that act as positive allosteric modulators were identified. In order to investigate the structural effect of these nanobodies, methods for expression and purification of full-length heteromeric GABAARs were then investigated. A comparison of transient transfection, BacMam and stable cell lines indicated that the highest expression was obtained from HEK293 cells stably transduced with triheteromeric GABAARs. After developing a method for purification of these receptors, the interaction of the α3β3γ2L GABAAR with one nanobody, α3β3nb173, was investigated by single-particle cryo-EM. Several datasets were collected, and the best map had a nominal resolution of 3.8 Å. This map revealed a novel modulatory site on the GABAAR, at the top of the β+/α- interfaces and above the GABA binding site. These findings have implications for the discovery of novel drugs against the GABAAR, potentially of major clinical importance, either by using nanobodies directly or developing compounds to mimic their activity at this novel site.